VENOUS RECONSTRUCTION AFTER IATROGENIC FEMOROILIAC INJURY: CASE REPORT - Ricardo Gouveia; Pedro Brandão; Victor Martins; Pedro Sousa; Jacinta Campos; Andreia Coelho; Rita Augusto; Nuno Coelho; Alexandra Canedo (Angiologia e Cirurgia Vascular, 2017)
Deep venous sector injuries during lower limb varicose vein surgery are rare. They can have serious repercussions in terms of the patient’s quality of life, so reconstructive interventions are strongly recommended. We report a case of a patient referred to our Institution after an extensive lesion of the femoral venous sector. We performed a reconstructive surgery, through mechanical thrombectomy, as he presented an extensive deep vein thrombosis, and by performing an interposition graft bypass. After two years of follow no complications were reported. The patient is asymptomatic, with no significant signs or symptoms of post thrombotic syndrome. The interposition graft is still patent.